THE CORRELATION BETWEEN STUDENTS’ SELF-EFFICACY AND THEIR SPEAKING ABILITY - Zakiyyatud Darojah; Zainul Aminin (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
This study aimed to investigate whether there is correlation between students’ self-efficacy and their speaking ability. A quantitative correlational research was employed in the present study. The sample of the current research was 60 students of 8th grade of SMP Bilingual Terpadu, one of bilingual junior high school in Sidoarjo. A questionnaire of self-efficacy in speaking was distributed to obtain students’ self-efficacy score. To acquire students’ speaking skill score, a speaking rubric was utilized. Pearson Product Moment Analysis was run to analyze the correlation between students’ self-efficacy and their speaking ability. The P value was less than 0.05 indicates there is significance correlation between both variables. Moreover, the correlation coefficient, r = 0.667, indicates a moderate degree of correlation.